2016
DOI: 10.1177/2325957415603507
|View full text |Cite
|
Sign up to set email alerts
|

Retention in Care of HIV-Positive Postpartum Females in Kumasi, Ghana

Abstract: Background Despite the success of prevention of mother-to-child transmission programs, transition to care in the postpartum period is vulnerable to being lost to care. Methods The authors performed a 2-year retrospective study of postpartum HIV-infected patients at Komfo Anokye Teaching Hospital in Kumasi, Ghana. The outcome was classified as optimal follow-up, suboptimal follow-up, and loss to follow-up (LTFU). Univariate and multivariate analyses were used to identify factors associated with optimal retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The proportion of women (67.4%) who remained in the PMTCT programme at 6 weeks postpartum is mostly consistent with a study in Ghana (66%) 32 and Rwanda (68.4%) 33 but slightly higher in (73.8%) KwaZulu Natal, a province in South Africa, 34 and the Democratic Republic of Congo (76.4%). 35 This rate may, however, be moderately high because of the short postpartum time; 6 weeks, under review as other studies have reported a decline in the proportion of women who remain in care at 6, 12 and 36 months postpartum.…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of women (67.4%) who remained in the PMTCT programme at 6 weeks postpartum is mostly consistent with a study in Ghana (66%) 32 and Rwanda (68.4%) 33 but slightly higher in (73.8%) KwaZulu Natal, a province in South Africa, 34 and the Democratic Republic of Congo (76.4%). 35 This rate may, however, be moderately high because of the short postpartum time; 6 weeks, under review as other studies have reported a decline in the proportion of women who remain in care at 6, 12 and 36 months postpartum.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, the suboptimal retention and viral suppression rates observed in our study were similar to those seen in postpartum women from other US populations studied before 2012, including in Philadelphia, PA [10], Jackson, MS [27], Houston, TX [17], and Chapel Hill, NC [13]. International studies report similar challenges in South Africa [28], Ghana [29], and Uganda [30] for example, with some successful interventions reported in the literature [3133]. Further, despite high levels of healthcare engagement during pregnancy, with an average number of prenatal care visits consistent with guidelines [34], retention and viral suppression among postpartum women in our study were even lower than those previously observed among men and women initiating HIV care in the same healthcare system, where 81% and 54% of patients were retained, and 63% and 44% were virally suppressed at 12 and 24 months, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Low retention in HIV care in the postpartum period has been shown across multiple studies in and outside of sub-Saharan Africa, with more than one in five recent mothers living with HIV not remaining in care six months after giving birth (1)(2)(3)(4)(5)(6). A systematic review also found that postpartum women living with HIV have lower ART adherence rates (57%) than pregnant women (75%) (7).…”
Section: Introductionmentioning
confidence: 98%